2001
DOI: 10.1016/s0896-6273(01)00445-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional Convergence of Response Properties in the Auditory Thalamocortical System

Abstract: One of the brain's fundamental tasks is to construct and transform representations of an animal's environment, yet few studies describe how individual neurons accomplish this. Our results from correlated pairs in the auditory thalamocortical system show that cortical excitatory receptive field regions can be directly inherited from thalamus, constructed from smaller inputs, and assembled by the cooperative activity of neuronal ensembles. The prevalence of functional thalamocortical connectivity is strictly gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
135
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(150 citation statements)
references
References 53 publications
15
135
0
Order By: Relevance
“…These methodological advances have allowed auditory neuroscientists to make significant progress in understanding the nature of the auditory computations that are found in the ascending processing stream of both birds [30,41,48,51,[58][59][60][61] and mammals [38,[62][63][64][65]. Selectivity for natural sounds is already present at the level of the inferior colliculus (IC) in the sense that IC STRFs show temporal spectral features that are found in behaviorally relevant sounds [38,41,[66][67][68].…”
Section: Methods For Estimating Strfs Using Natural Soundsmentioning
confidence: 99%
“…These methodological advances have allowed auditory neuroscientists to make significant progress in understanding the nature of the auditory computations that are found in the ascending processing stream of both birds [30,41,48,51,[58][59][60][61] and mammals [38,[62][63][64][65]. Selectivity for natural sounds is already present at the level of the inferior colliculus (IC) in the sense that IC STRFs show temporal spectral features that are found in behaviorally relevant sounds [38,41,[66][67][68].…”
Section: Methods For Estimating Strfs Using Natural Soundsmentioning
confidence: 99%
“…The lack of such sensitivity in auditory thalamus, for the same stimulus parameters for which it was clearly present in A1, implies a function that is unique to A1. Many years of research have indicated that the performance of A1 neurons is not better than, and is probably even worse than, subcortical neurons, when comparing standard measures of sensory coding such as width of tuning curves and temporal response properties (Creutzfeldt et al, 1980;Miller et al, 2001;Joris et al, 2004). Therefore, we propose that we need to consider higher-level functions, such as sensory memory, if we want to understand the role of A1 in auditory processing.…”
Section: Mechanisms Of Adaptationmentioning
confidence: 99%
“…It has been suggested that certain synaptic properties and connectivity patterns of PAC are specific for extracting spectrotemporal feature information [13][14][15] . Hence, information processing of visual system and that of the auditory system may be quite different.…”
Section: Visual "What" and "Where" Segregation Pathwaysmentioning
confidence: 99%